Three-dimensional free-radical polymerization : cross-linked and hyper-branched polymers - Korolev, G. V. (Springer, 2017)
The book discusses the latest developments in the entire field of three-dimensional free-radical polymerization. It is the first book on the subject comprising the research results of the last 40 years and will benefit the specialist in new high-tech areas